Norm og usus - betragtninger over en russisk-færøsk ordbog - Thomsen, Johnny (Nordiske Studier i Leksikografi, 2014)
The paper deals briefly with a crucial problem of Faroese, namely the dichotomy between a principally purist codified variety of the language and an uncodified variety, teeming with Danish-German loanwords and internationalisms, and its lexicographical treatment. The prevailing purist lexicographical attitude towards Faroese has led to significant parts, numerically and denotatively, of the Faroese lexicon being excluded from Faroese dictionaries as well as to inclusion of rare neologisms, idiolectisms, and ad hoc coinages as entries and translations. A different approach, exemplified by a forthcoming Russian-Faroese dictionary, which recognizes the entire register variation of Faroese, including the uncodified lexicon, is discussed.